Antibacterial Activity of Ethanolic Extract of Cardiospermum halicacabum against Methicillin-Resistant Staphylococcus aureus - Meesil, Wipanee; Wisuitiprot, Wudtichai; Ngoenkam, Jatuporn; Muangpat, Paramaporn; Teethaisong, Yothin; Sittisak, Sutthirat; Vitta, Apichat; Thanwisai, Aunchalee (Trends in Sciences, 2024)
We investigated the antibacterial activity of Cardiospermum halicacabum extract against methicillin-resistant Staphylococcus aureus (MRSA) via the disk diffusion method and identified the plant’s bioactive phytochemicals. Additionally, we evaluated the synergistic effects, and primary mechanism of action of the plant extract against the S. aureus strain PB57 (MRSA). The ethanolic extract of C. halicacabum contained beneficial secondary metabolites such as the flavonoids apigenin, terpenoids and tannins. The total phenolic content, expressed as the gallic acid equivalent (g GAE/kg), was 87.66 ± 14.56 g GAE/kg at a concentration of the 1 mg/mL. The plant extract inhibited and killed the S. aureus strain PB57 with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 0.98 mg/mL. Electron microscopy revealed that the plant extract caused damage to the ultrastructures of the cells of the pathogens. The compounds in the extract remained below known maximum acceptable cytotoxicity thresholds for fibroblast cells, which are typically in the range of [include specific value from relevant guidelines or literature]. Further cytotoxicity assays are required to determine the precise safety margins for therapeutic use. Although the extract showed promise against MRSA, its application as a broad treatment for infectious diseases requires more specific testing on other pathogens. Based on the scope of our research, C. halicacabum could be a viable candidate for the development of treatments targeting MRSA-related infections. HIGHLIGHTS Our investigation revealed that the ethanolic extract of Cardiospermum halicacabum exhibited significant antibacterial activity against the methicillin-resistant Staphylococcus aureus (MRSA) strain PB57. The extract contained beneficial secondary metabolites, including flavonoids such as apigenin, as well as terpenoids and tannins. Moreover, the electron microscope shown that the extract disrupted the pathogen’s cell structures and, despite showing some cytotoxicity at higher doses, remained within safe limits, positioning C. halicacabum as a potential treatment for infectious diseases. GRAPHICAL ABSTRACT